Diffusion coefficient of K+ in ion exchanged glasses calculated from the refractive index and the Vickers hardness profiles - Saggioro, B. Z.; Ziemath, E. C. (Elsevier B.V., 2006)
The top faces of float glass samples were exposed to vapors resulting from the decomposition of KNO3 at 565 degrees C for up to 32 h. X-ray dispersive spectra (EDS) show that K+ ions migrate into the glass. The K+ concentration profile was obtained and its diffusion coefficient was calculated by the Boltzmann-Matano technique. The mean diffusion coefficient was approximately 10 X 10(-11) cm(2) s(-1). It was observed that the refractive index and the Vickers hardness decrease with the depth (after the removal of successive layers), and their profiles were thus obtained. These profiles enabled the calculation of the diffusion coefficient of K+ through the Boltzmann-Matano technique, with mean results ranging between 6 x 10(-11) and 30 x 10(-11) cm(2) s(-1). (c) 2006 Elsevier B.V. All rights reserved.
Keywords: ion exchange; SEM; hardness